IDENTIFICATION OF MYCOBACTERIUM TUBERCULOSIS (MTB) IN SPUTUM OF PATIENTS WITH COUGH ≥ 2 WEEKS USING ZIEHL- NEELSEN STAINING METHOD AT RSUD SITI FATIMAH AZ-ZAHRA PALEMBANG IN 2025 - M Nabil; Teni Nopita Sari (PT. Jurnal Center Indonesia Publisher, 2026)
Tuberculosis remains a major public health problem in Indonesia with high morbidity and mortality rates. This study aimed to identify Mycobacterium Tuberculosis (MTB) in sputum samples of patients with productive cough lasting ≥ 2 weeks using the Ziehl-Neelsen staining method at RSUD Siti Fatimah Az- Zahra Palembang. This study uses a descriptive observational method with a cross-sectional approach and involves 30 respondents. The results showed that all respondents experienced cough, with the majority 24 respondents (80.0%) having productive cough ≥ 2 weeks and 6 respondents (20.0%) having prolongrd cough < 2 weeks. Sputum examination revealed 17 respondents (56.7%) were Acid-Fast Bacilli (AFB) positive, while 13 respondents (43.3%) were negative. These findings indicate that a prolonged cough lasting ≥ 2 weeks is associated with AFB-positive results, although tuberculosis may also occur in patients with prolonged cough lasting < 2 weeks. It is recommended that patients with positive results undergo complete DOTS therapy, hospitals improve diagnostic services and health education, communities adopt a healthy lifestyle, and further research be conducted to explore the underlying causes of prolonged cough.